2021
DOI: 10.1111/tbed.14075
|View full text |Cite
|
Sign up to set email alerts
|

Human brucellosis epidemiology in the pastoral area of Hulun Buir city, Inner Mongolia autonomous region, China, between 2003 and 2018

Abstract: Human brucellosis represents a serious public health concern in Hulun Buir and requires a comprehensive epidemiologic analysis to define adapted control measures. The present study describes the case numbers, constituent ratios and incidence rate of human brucellosis. Conventional biotyping, that is abortus, melitensis, ovis and suis (AMOS)‐PCR and multi‐locus variable‐number tandem repeat analysis (MLVA) were used to characterize the Brucella strains. Between 2003 and 2018, a total of 23,897 human brucellosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In this study, we identified a strong correlation between the infection site of human brucellosis and all utilization categories examined, emphasizing the importance of considering this factor when assessing the economic burden of human brucellosis. Notably, few previous studies in China have specifically investigated the cost implications associated with the infection site ( 28 , 29 ), highlighting a critical knowledge gap. This study contributes to filling this void by providing detailed insights into how the location of infection impacts various cost components.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we identified a strong correlation between the infection site of human brucellosis and all utilization categories examined, emphasizing the importance of considering this factor when assessing the economic burden of human brucellosis. Notably, few previous studies in China have specifically investigated the cost implications associated with the infection site ( 28 , 29 ), highlighting a critical knowledge gap. This study contributes to filling this void by providing detailed insights into how the location of infection impacts various cost components.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that the nomadic lifestyle (which often involves the consumption of raw milk) and production methods (e.g., homemade dairy products) in highland pastoral areas may have caused these infection events, and a detailed field survey is needed to verify the conclusion of this molecular investigation. A nomadic lifestyle may favor the spread of brucellosis among different animals and populations ( Liu et al, 2022 ) because animals and people live in close contact. A 2018 report found that the consumption of raw milk from smuggled sick goats caused human brucellosis epidemics (25 cases) in Douz, Tunisia ( Charaa et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%